THE EFFECT OF SCIENTIFIC INQUIRY LEARNING MODEL AND CREATIVE THINKING ABILITY ON SCIENCE PROCESS SKILLS OF STUDENT - Puji Anggraini; Ridwan Abdullah Sani (Jurnal Pendidikan Fisika, 2015)
The aims of this research were to analyze science process skills of students using scientific inquiry Learning Model is better than science process skills of students using conventional learning, analyze science process skills of students who have high category in creative thinking ability better than low category in creative thinking ability, and analyzethe interaction between scientific inquiry learning and the level of creative thinking ability in improving the science process skills. The research type was quasi experiment and two group pretest-posttest designs were used in this study. The population of the study was grade X of SMAN 1 Stabat Academic Year 2014/2015. The sample was chosen by using cluster random class technique. The sample was divided into two classes, the experiment class taught by scientific inquiry and control class taught by conventional learning. The instrument was consisting of science process skills test and creative thinking ability test. Data in this research was analyzed by using two way ANOVA. The results of this research showed that the scientific inquiry learning model was better than conventional learning in improving the students science process skills, the science process skills of the students who had high category in creative thinking ability was better than low category, and there was interaction between scientific  inquiry learning model and the level of creative thinking ability in  improving students science process skills.